Robótica educacional sem a utilização de microcontroladores - Borça, João Pedro (2018)
Educational robotics used as a teaching tool, using computers, microcontrollers and other electronic components, aims to explore concepts from several areas of knowledge. This article reports the use of digital technologies along with their benefits when applied in the educational field,and proposes a simple robotics competition with 2 practical activities, without the use of programmable microcontrollers, with cheap and easily accessible components, proposing to be the first contact of students with activities related to robotics.